2013
DOI: 10.9790/0853-0366870
|View full text |Cite
|
Sign up to set email alerts
|

High division and variation in brachial artery branching pattern.

Abstract: :In a 45 year male cadaver unusual variation of right brachial artery branching was observed.Brachial artery also showed high division in to radial and ulnar artery in upper third of arm. The posterior circumflex humeral artery, profunda brachii artery and superior ulnar collateral artery all arose from one common trunk in proximal part of brachial artery before its termination. In this report we endeavor to discuss the relevance of embryogenesis and clinical importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…High origin of radial artery occurrence is 3 to 15%, as reported by different authors. The parent trunk being axillary artery in 12.5%, proximal 1/3 of brachial artery in 62.5% and middle 1/3 of brachial artery in 25% [8].…”
Section: Resultsmentioning
confidence: 98%
“…High origin of radial artery occurrence is 3 to 15%, as reported by different authors. The parent trunk being axillary artery in 12.5%, proximal 1/3 of brachial artery in 62.5% and middle 1/3 of brachial artery in 25% [8].…”
Section: Resultsmentioning
confidence: 98%
“…High origin of radial artery occurrence is 3 to 15 % (7 & 8) and that of ulnar artery is 1 % (7). High division of brachial artery into its terminal branches may occur at any point in the normal course of the vessel, but it is more common in the middle third (7). If the two vessels run parallel to each other to the elbow in the usual position of the brachial artery and from this point, one branch follows the normal course of radial artery and the other one takes the normal course of the ulnar artery, this arrangement is considered a simple high division of the brachial artery (7).…”
Section: Discussionmentioning
confidence: 99%
“…Teli et al (7) reported a case where the brachial artery divided into its terminal branches in the upper third of the arm, about 1.5 cm distal to the lower border of teres major. They classified the variation as superficial brachioradial artery, which is high origin of radial artery with course superficial to forearm flexors.…”
Section: Discussionmentioning
confidence: 99%
“…This is because of their multiple and plexiform sources of origin, the temporal succession of emergence of principal arteries, anastomosis and periarterial network & functional dominance followed by regression of some paths [5]. Persistence of embryological vessels may be the basis of SBA.…”
Section: Discussionmentioning
confidence: 99%